МІНІМІЗАЦІЯ ВПЛИВУ НАСИЧЕННЯ МАГНІТОПРОВОДІВ ТРАНСФОРМАТОРІВ СТРУМУ НА ТОЧНІСТЬ ВИСОКОВОЛЬТНИХ ТРИФАЗНИХ ПЕРВИННИХ ВИМІРЮВАЛЬНИХ КАНАЛІВ З ЦИФРОВИМ ВИХОДОМ - Паньків, В.І.; Танкевич, Є.М.; Танкевич, С.Є. (Інститут електродинаміки НАН України, Київ, 2021)
The classification is carried out and the characteristics, capabilities and disadvantages of the known methods of programmed correction of the output current of a single-phase primary measuring channel (PMC) of the current are determined. A discretized model of short-circuit current (SCC) is proposed. A method and an algorithm for increasing the accuracy of a three-phase current PMC in transient modes of electric power systems (EPS) under the condition of saturation of the magnetic circuits of its phase current transformers have been developed. The reliability of the developed method is confirmed by simulation of the PMC output current under the condition of phase-to-phase short-circuit of phases A and B without correction and with correction of its phase currents. It is shown that the developed method makes it possible to reduce the total error of the PMC in the transient modes of the EES under the condition of saturation of the magnetic circuits of the CT from 70-90% to 6-15%. References 47, figures 6, table 1.